2019
DOI: 10.3390/jcm8122221
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postoperative Opioid Consumption and Pain Scores in Primary Versus Repeat Cesarean Delivery in Opioid Naïve Patients

Abstract: Background: Cesarean deliveries represent a large percentage of deliveries worldwide. Patients undergoing repeat cesarean deliveries are known to have increased risks for surgical complications. However, little is known regarding potential differences in pain. We sought to compare postoperative opioid consumption and pain scores in opioid naïve patients undergoing primary versus repeat non-emergent cesarean delivery. Methods: This was a retrospective cohort study. Patient inclusion criteria included: having a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Uterine contraction pain is a form of visceral pain, which is characterized by inaccurate positioning, and mainly manifested as paroxysmal colic, mostly caused by postpartum uterine involution and paroxysmal contractions. Compared with a first cesarean section, patients receiving a second cesarean section have more severe, long-lasting, and frequent contractions and hyperalgesia (4)(5)(6). At present, PCIA is usually used clinically for postoperative analgesia of cesarean section.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uterine contraction pain is a form of visceral pain, which is characterized by inaccurate positioning, and mainly manifested as paroxysmal colic, mostly caused by postpartum uterine involution and paroxysmal contractions. Compared with a first cesarean section, patients receiving a second cesarean section have more severe, long-lasting, and frequent contractions and hyperalgesia (4)(5)(6). At present, PCIA is usually used clinically for postoperative analgesia of cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated on the basis of a pilot study that showed the effect of acupressure on labor pain intensity and labor duration (13). The VAS score for significant pain reduction during labor was one score based on visual analogue scale (6,14). Using the PASS software 15.0, α=0.05, and power =0.85, considering SD =1.4 and M0 =7.2 for the labor pain score and 10% drop out of subjects, the sample size was calculated to be 36 patients for each group.…”
Section: Sample Size Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…18 However, limited documentation of pain assessment and reassessment was observed. 19 The most used post-operative pain assessment tools are unidimensional and assess only pain intensity, which is just one aspect of the sensory dimension. 20 These include the Numerical Rating Scale (NRS) and the VRS.…”
Section: Discussionmentioning
confidence: 99%
“…Acute postsurgical pain has been associated with patient (e.g., age, preexisting psychiatric diagnoses, body mass index, smoking status), surgical (e.g., planned versus unplanned CD, primary versus repeat CD, operative time), and anesthetic (general versus regional anesthesia) factors [4][5][6][7][8][9]. Pre-procedural identification of women at increased risk for pain following CD can be used to optimize analgesia and potentially attenuate development of chronic effects [10].…”
Section: Introductionmentioning
confidence: 99%